COMPARATIVE STUDY OF ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF SPICES ALONG WITH STRUCTURAL DETERMINATION USING FT-IR SPECTROSCOPY - ANUSHREE CHOWDHURY; KRITIKA AGGARWAL; RAJAM CHIDAMBARAM (International Journal of Pharma and Bio Sciences, 2013)
In today’s medical world, antibiotic toxicity and multidrug resistant pathogens are the two greatest challenges which require immediate attention. In the present study, the antibacterial and antioxidant activity of spices have been investigated. The antibacterial activity of eight common Indian spices was analyzed against nine clinical pathogenic bacteria by Kirby Bauer Disc Diffusion method and maximum inhibition concentration (MIC) was determined. Maximum inhibition zones in the range of 17-25mm were seen in extracts of star anise and asafoetida. The antibacterial effect was also compared with the standard antibiotic discs. The antioxidant activity was evaluated by free radical scavenging power against DPPH free radical. The IC50 of the methanolic extracts ranged from 4.45 ± 0.1 to 19.6 ± 0.4 μg/ml and that of control i.e. ascorbic acid was 6.01 ± 0.1 μg/ml. Qualitative estimation was done by FT-IR analysis and major functional groups present in spices were determined.